Macroinvertebrate assessment in seagrass ecosystem in Sinacaban Municipality, Misamis Occidental, Philippines - HEIZEL MAE O. MAHILAC; JOYLINBER P. TANDINGAN; ARMI G. TORRES; RUBEN AMPARADO JR; HILLY ANN ROA-QUIAOIT (Society for Indonesian Biodiversity, 2023)
Abstract. Mahilac HMO, Tandingan JP, Torres AG, Amparado JRR, Roa-Quiaoit HA. 2023. Macroinvertebrate assessment in seagrass ecosystem in Sinacaban Municipality, Misamis Occidental, Philippines. Biodiversitas 24: 5586-5597. Marine ecosystems such as seagrasses are economically and ecologically important in tropical coastal areas like Sinacaban municipality, southern Philippines. This study assessed the macrobenthic species and water quality (e.g., pH, salinity, temperature, Dissolved Oxygen (DO), and total suspended solids (TSS) in three seagrass areas in the municipality. The study showed the seagrass habitats with 40 macrofaunal species from the classes Gastropoda (27), Bivalvia (11), and Crustacea (2), with Clibanarius longitarsus as the most abundant species (77 individuals or 24% relative abundance). The Strombidae family holds the highest dominance within the Gastropoda class, whereas the Arcidae family is the most dominant within the Bivalvia class. However, there is no dominant family within the Crustacea class. Water quality showed pH at 7, 30 ppt salinity, and 28? within their standard limits, while DO (8 mg/L) and TSS (127 mg/L) exceeded their range. This study recorded eight economic important species and five least concern International Union for Conservation of Nature (IUCN) species. Among the three (3) sites, the seagrass area in Libertad has the highest species richness (28), Shannon’s Index (2.92), and species evenness (0.66). The Chao estimation result revealed that Libertad (37.17) and Poblacion (18.5) have lower uncertainty in their species estimates than Colupan (39.60), which has a wider range of potential species richness. The Canonical Correspondence Analysis (CCA) proved that there are species that can adapt to a certain level of environmental parameters, like Angaria delphinus, while Decatopecten radula is one of the species that does not correlate with the water parameters in the study. The findings are critical for biodiversity conservation, ecosystem management, sustainable resource use, and adaptation to changing environments in order to maintain ecological balance and the long-term health of the seagrass ecosystem.